McEnvoy’s Handbook of Photovoltaics-Fundamentals and Applications - (:unkn) unknown (My University, 2017)
Practical Handbook of Photovoltaics, Third Edition, is a 'benchmark' publication for those involved in the design, manufacture and use of these devices. This fully revised handbook includes brand new sections on smart grids, net metering and the modeling of photovoltaic systems, as well as fully revised content on developments in photovoltaic applications, the economics of PV manufacturing and updated chapters on solar cell function, raw materials, photovoltaic standards, calibration and testing, all with new examples and case studies. The editor has assembled internationally-respected contributors from industry and academia around the world to make this a truly global reference. It is essential reading for electrical engineers, designers of systems, installers, architects, policymakers and physicists working with photovoltaics.
Keywords: Solar radiation; Photovoltaic systems